Covid-19 and Vote Buying in Direct Regional Head Elections - Mohammad Hidayaturrahman; Sudarman Sudarman; Ahmad Hasan Ubaid; Elazhari Elazhari; Aryo Wibisono; Faqih Alfian (Universitas Muhammadiyah Yogyakarta, 2022)
The current covid-19 pandemic has killed tens of millions people. One way to avoid covid-19 is to keep a distance from each other. At at the same time, Indonesia actually held direct regional head elections in 270 regions, which required voters to come and gather at the polling station (TPS). This research was conducted to analyze the relationship between covid-19 and vote buying with voters participation in direct regional head elections in Indonesia, which was held on December 9, 2020. For the research approach, mixed methods both quantitative and qualitative descriptive were used. The quantitative method was carried out by distributing questionnaires directly to 139 polling stations in Sumenep Regency, East Java, during the regional head election. While the qualitative method is carried out by observing directly the conditions at the polling station (TPS). In addition, in-depth interviews with the election committee and voters were also conducted. The results of the study found that voter participation was very high even though the regional head election was held during the covid-19 pandemic. This high participation was apparently correlated with the widespread practice of vote buying carried out by the winning team for the two pairs of regional head candidates.